The power of retrotransposons in high-throughput genotyping and sequencing - Arvas, Yunus Emre; Marakli, Sevgi; Kaya, Yılmaz; Kalendar, Ruslan (Frontiers in Plant Science, 2023)
The use of molecular markers has become an essential part of molecular genetics through their application in numerous fields, which includes identification of genes associated with targeted traits, operation of backcrossing programs, modern plant breeding, genetic characterization, and marker-assisted selection. Transposable elements are a core component of all eukaryotic genomes, making them suitable as molecular markers. Most of the large plant genomes consist primarily of transposable elements; variations in their abundance contribute to most of the variation in genome size. Retrotransposons are widely present throughout plant genomes, and replicative transposition enables them to insert into the genome without removing the original elements. Various applications of molecular markers have been developed that exploit the fact that these genetic elements are present everywhere and their ability to stably integrate into dispersed chromosomal localities that are polymorphic within a species. The ongoing development of molecular marker technologies is directly related to the deployment of high-throughput genotype sequencing platforms, and this research is of considerable significance. In this review, the practical application to molecular markers, which is a use of technology of interspersed repeats in the plant genome were examined using genomic sources from the past to the present. Prospects and possibilities are also presented.